Should temozolomide be used on the basis of O6-methylguanine DNA methyltransferase status in patients with advanced neuroendocrine tumors? A systematic review and meta-analysis. (September 2021) - Trillo Aliaga, P.; Spada, F.; Peveri, G.; Bagnardi, V.; Fumagalli, C.; Laffi, A.; Rubino, M.; Gervaso, L.; Guerini Rocco, E.; Pisa, E.; Curigliano, G.; Fazio, N.
Highlights: Temozolomide (TEM) is an active treatment in metastatic neuroendocrine tumors (NETs). The predictive role of deficiency of O 6 -methylguanine DNA methyltransferase (MGMT) in patients with NETs treated with TEM is still under debate. In our pooled analysis we observed higher ORR, longer PFS and OS in patients with NETs with MGMT-deficiency compared to MGMT-proficiency. Based on these results, future homogeneous prospective clinical trials are warranted. Abstract: Background: Temozolomide (TEM) is an active treatment in metastatic neuroendocrine tumors (NETs). Patients affected by glioblastoma multiforme or advanced melanoma treated with TEM who have deficiency of O 6 -methylguanine DNA methyltransferase (MGMT) have a better responses and survival. However, the predictive role of MGMT in patients with NETs treated with TEM is still debated. Methods: We conducted a systematic review of the literature and meta-analysis, based on PRISMA methodology, searching in the main databases (PubMed, Embase, Scopus, Web of Science, Cochrane Library and clinical trial.gov) and the proceedings of the main international congresses, until April 26, 2021. Results: Twelve out of 616 articles were selected for our analysis, regarding a total of 858 NET patients treated with TEM-based chemotherapy. The status of MGMT had been tested in 513 (60%) patients, using various methods. The pooled overall response rate (ORR) was higher in MGMT-deficient compared with MGMT-proficient NETs, with a risk difference of 0.31 (95% confidence interval, CI: 0.13–0.50; p < 0.001; I 2 : 73%) and risk ratio of 2.29 (95% CI: 1.34–3.91; p < 0.001; I 2 : 55%). The pooled progression free survival (PFS) (hazard ratio, HR = 0.56; 95% CI: 0.43–0.74; p < 0.001) and overall survival (OS) (HR = 0.41; 95% CI: 0.20–0.62; p = 0.011) were longer in MGMT-deficient versus MGMT-proficient NETs. Conclusions: Our meta-analysis suggested that MGMT status may be predictive of TEM efficacy. However, due to the high heterogeneity of the evaluated studies the risk of biases should be considered. On this hypothesis future homogeneous prospective studies are warranted.